From Individual Learning to Interorganizational Learning: Proposition of an Analysis Framework - Vania de Fátima Barros Estivalete (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The focus of this study is in the search for trying to understand how the individual, organizational and interorganizational learning processes occur in two horizontal networks of the agribusiness retail chain that belong to the supermarket segment. Therefore, the objectives of this paper are: (i) suggesting a learning process analysis framework among organizations that establish horizontal interorganizational relationships, articulating learning on the individual, organizational and interorganizational levels, and applying it to networks, and; (ii) establishing relationships between the constructs and the categories that constitute the framework. This research is characterized by its qualitative and exploratory nature, and the method adopted is the study of multiple cases. The data were collected through questionnaires, interviews, documental analysis and learning stories. In order for the learning process to advance on an interorganizational level, the research results indicated the importance of: strategic behaviors related to collaboration; learning through the interactive method and; greater valorization of the learning elements of the behavioral-social dimension, mainly the key element of trust in the relationships.